2021
DOI: 10.3390/jcm10215019
|View full text |Cite
|
Sign up to set email alerts
|

What Do We Know about Inequalities in NAFLD Distribution and Outcomes? A Scoping Review

Abstract: With prevalence high and rising given the close relationship with obesity and diabetes mellitus, non-alcoholic fatty liver disease (NAFLD) is progressively becoming the most common chronic liver condition worldwide. However, little is known about the health inequalities in NAFLD distribution and outcomes. This review aims to analyze health inequalities in NAFLD distribution globally and to assess the health disparities in NAFLD-related outcomes. We conducted a scoping review of global health inequalities in NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 57 publications
(117 reference statements)
2
16
0
Order By: Relevance
“…Strengthening education and communication, raising public awareness, and developing sound disease classification criteria and long-term prevention plans (including for obesity and type 2 diabetes) are urgent priorities for Latin America to address their challenges with NAFLD ( 47 , 48 ). NAFLD is a multifactorial disorder influenced by individual behaviors and genetics, as well as cultural, demographic, economic, medical, and environmental influences ( 49 ). The recent diet trends of excessive energy intake and sedentary lifestyles, and unbalanced medical resources can somewhat explain the differences among the five SDI subgroups ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Strengthening education and communication, raising public awareness, and developing sound disease classification criteria and long-term prevention plans (including for obesity and type 2 diabetes) are urgent priorities for Latin America to address their challenges with NAFLD ( 47 , 48 ). NAFLD is a multifactorial disorder influenced by individual behaviors and genetics, as well as cultural, demographic, economic, medical, and environmental influences ( 49 ). The recent diet trends of excessive energy intake and sedentary lifestyles, and unbalanced medical resources can somewhat explain the differences among the five SDI subgroups ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…As for NAFLD, in a previous study 15 we found that very few studies investigating socioeconomic determinants of health and inequality on NAFLD had been published, almost all of them in the US, where Hispanic ethnicity has been associated with a higher prevalence of NAFLD and poorer outcomes and female sex has been associated with a lower chance of receiving a liver transplant once cirrhosis develops. Moreover, low socioeconomic status was associated with a higher NAFLD prevalence (4 articles) and a higher likelihood of progression and complications.…”
Section: Inequalities By Liver Diseasementioning
confidence: 98%
“…Patients with low socioeconomic status had higher NAFLD prevalence and a higher likelihood of progression and complications. 15 Educational programmes delivered at schools on the harms of a sedentary lifestyle on fat-rich sugar-rich diets, including a clear portrayal of obesity as a disease. Obesity should be tackled by community health programmes in which parents are engaged.…”
Section: Liver Transplantationmentioning
confidence: 99%
“…NAFLD/NASH prevalence is epidemiologically linked to multiple social determinants of health, including poverty, food or housing insecurity, and poor access to healthcare ( Talens et al, 2021 ). Patients experiencing poor determinants of health also have a higher prevalence of NAFLD-associated traits including insulin resistance, obesity, and metabolic syndrome ( Cho et al, 2021 ).…”
Section: Mechanistic Synergies Between Non-alcoholic Fatty Liver Dise...mentioning
confidence: 99%